Pearl‐unjammed: the Seattle stone maneuver for ureteropelvic junction urolithiasis. Issue 3 (25th March 2020) - Hall, M. Kennedy; Samson, Patrick C.; Kessler, Ross; Lehnhardt, Kris; Easter, Benjamin; Thiel, Jeff; Wessells, Hunter; Bailey, Michael R.; Harper, Jonathan D.
Abstract: Renal colic encounters are common; in the United States alone, they represent greater than one million annual emergency department (ED) visits. Most of these stones are managed conservatively with a trial of passage. However, some lead to repeat colic episodes, secondary ED visits, increased anxiety, and increased cost. Of the 5%–10% of symptomatic stones that become lodged at the ureteropelvic junction and are larger than 5 mm, most require operative intervention. In the process of executing a NASA‐funded study of ultrasonic repositioning of kidney stones, the subject was administered fluid to dilate the collecting system, placed in Trendelenburg bed positioning, and rolled to both sides. During this process a symptomatic, obstructing 9‐mm ureteropelvic junction stone moved back into the kidney's lower pole/infundibulum and symptoms were immediately resolved. The patient remained asymptomatic for a period of 5 weeks at which point elective intervention was scheduled. This case demonstrates that ureteropelvic junction stones may be repositioned in a non‐invasive manner, turning a stone that requires urgent intervention into one that can be managed electively.